Defining the Role of the Tibial Tubercle–Trochlear Groove and Tibial Tubercle–Posterior Cruciate Ligament Distances in the Work-up of Patients With Patellofemoral Disorders. (June 2015) - Anley, Cameron Michael; Morris, Guy Vernon; Saithna, Adnan; James, Steven Laurence; Snow, Martyn
Background: The radiological work-up of patients with patellofemoral disorders continues to be debated. The interchangeability of the tibial tubercle–trochlear groove (TT-TG) distance between computed tomography (CT) and magnetic resonance imaging (MRI) has recently been questioned. In addition, a new measurement—the tibial tubercle–posterior cruciate ligament (TT-PCL) distance—has shown that not all patients with a pathological TT-TG distance (>20 mm) have lateralization of the tibial tubercle. Another factor to consider when looking at the position of the tibial tubercle is the knee joint rotation, defined as the angle between the femoral dorsal condylar line and the tibial dorsal condylar line. Purpose: To determine, with a larger population, if the TT-TG measurements can be used interchangeably between CT and MRI and to confirm the correlation between the TT-PCL and TT-TG distances in determining tibial tubercle lateralization. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Patients with patellofemoral disorders and MRI and CT scans of the same knee (n = 141) were identified. The TT-PCL, the knee joint rotation, and TT-TG were measured independently by 2 fellowship-trained orthopaedic surgeons. Thirty measurements were repeated on a separate occasion to allow for an assessment of the intrarater reliability. The intraclass correlation coefficient (ICC) was used to assess reliability of the measurements. Results: The mean TT-TG was 4.16 mm less on MRI ( P < .05), with the mean TT-TG ± SD being 17.72 ± 5.15 mm on CT (range, 6.97-31.33 mm) and 13.56 ± 6.07 mm on MRI (range, 2-30.04 mm). The ICC for each rater comparing the 2 imaging modalities was only fair (0.54 and 0.48). The mean TT-PCL measurement was 20.32 ± 3.45 mm (range, 10.11-32.01 mm) with excellent interobserver and intraobserver reliability (>0.75). Based on the TT-TG and TT-PCL measurements, 4 groups of patients can be established. When knee joint rotation is compared among groups, an increased TT-TG may result from true lateralization of the tibial tubercle, an increased knee joint rotation, or both. Conclusion: Based on a statistically significant mean difference (4.11 mm) and only a fair ICC (0.54 and 0.48) for raters comparing the 2 modalities, the measurements for the TT-TG cannot be used interchangeably between CT and MRI. Therefore, currently accepted values for TT-TG based on CT scans should not be applied to an MRI scan. The TT-PCL measurement is a measure of true lateralization of the tibial tubercle, while the TT-TG is an amalgamated measure of true lateralization and knee joint rotation.